Decisive generations of ucevistas in the conformation of the modern cosmovisión in Barquisimeto 1814-1858 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
The research presented below represents the effort to understanding the way the modern worldview developed in the city of Barquisimeto during the first half of the 19th century. It thus responds to a history of metaphysics, namely a historical ontology deeply rooted in the new project of being that was forged by the end of the colonial period in these regions of tierraadentro (inland). As any society is never contemporary with regards to all of its members, this project of being is embodied, in fact, in a given generation. It first appears in very few members, then it gradually spreads throughout the whole of society until it settles in the main political, economic, religious, legal, health and school positions, until it slowly but surely becomes ideology. Such ideology will become the main way of understanding world and therefore, also simplest dailylife situations such as measuring, planning, calculating and managing.A reflection that aims to explore the historical and ontogenetic root of such a decisive phenomenon, by removing the patina of its tiresome ideological condition, bringing back at the same time the living light of truth, revealing even in its path, the rejection or acceptance of aforementioned modern worldview project, becomes paramount.It is therefore a central objective of this research to witness firsthand the genesis and unfolding of the way the modern worldview developed in the city of Barquisimeto, and also to analyze how it spread through school systems.In this sense, the activity of the Pontifical University of Santiago de León de Caracas, later the Central University of Caracas, today simply UCV, carried out a fundamental task.We have relied entirely on Martin Heidegger's metaphysical, historical and methodological conceptions, as well as on the method of the generations proposed by José Ortega y Gasset.Let this be a favorable opportunity to pay a sincere tribute to the Central University of Venezuela (1721-2021) for its egregian work of almost three hundred years, as well as to all the Universities and the university lecturers from all over the country who fight and have devoted their lives to keep alive the burning flame for research amid the deplorable conditions to which the philistines in spirit have led us.Maintaining this very flame of investigation is, aristotelian speaking, exercising the essence of freedom factually.
Keywords: worldview; generations; project of being; modernity; education